The man in the high castle - Dick, Philip K. (Mariner Books, 2011)
It's America in 1962. Slavery is legal once again. The few Jews who still survive hide under assumed names. In San Francisco, the I Ching is as common as the Yellow Pages. All because some twenty years earlier the United States lost a war -- and is now occupied by Nazi Germany and Japan.